DESCRIPTION OF 13 RARE INDONESIAN PHONECARD SETS IN FOLDERS FROM ’90S ASSOCIATED TO TELECOMMUNICATIONS - Wagner de Souza Tavares; Rani Uli Silitonga (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2022)
A few number of Indonesian phonecards are available in folders with several in low mintage. A catalog listing Indonesian phonecards available in folders and packs is unavailable. The objective was to describe 13 rare Indonesian phonecard sets in folders associated to telecommunications. The rarity of the folders was defined based on their low mintage. The folders were described, photographed, classified, and measured (cm). The phonecard folders were successfully described. The mintage varied from 300 to 5000 units. The description of rare Indonesian phonecards available in folders is important as a memory of the rich Indonesian art and culture in phonecards.